Red guards and political dissidents (I): Tools of violence and power struggle - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
In 1966, Mao Zedong launched the Great Proletarian Cultural Revolution in a last attempt to remake China in his image. He believed that the country was led by a party infested from the top on down with “capitalist-roaders” who had betrayed the proletarian goals of true socialism by following the bourgeois line. Denied support in the power structure, Mao sought help from the outside, mobilizing millions of high school and college students as the “Red Guards” to strike down his enemy in an unprecedented campaign that left the nation nearly paralyzed. Red Guard organizations of confusing ideological persuasions soon proliferated throughout the country, and the whole movement quickly got out of control and degenerated into total chaos. That the Red Guards were used by Mao as a tool in the ideologically based power struggle within the party is not only the consensus of most observers but also has been freely admitted by many former Red Guards. © 1988 by Taylor & Francis. All rights reserved.
Journal Abbreviation: Hum. Rights in the People's Repub. of China
Keywords: dept.his